PERAN BRAND AWARENESS DALAM MEMEDIASI HUBUNGAN IKLAN DAN PERSONAL SELLING DENGAN NIAT BELI - Prabawa, Kadek Teddy Surya; Sukawati, Tjok Gde Raka; Setiawan, Putu Yudi (E-Jurnal Manajemen, 2017)
The number of foreign insurance companies who compete in the growth of life insurance market in Indonesia increased continually making AJB Bumiputera 1912 lose the competition in terms of purchase intention and brand awareness. The aim of this research was to determine the role of brand awareness in mediating the relationship between advertising and personal selling with purchase intention. This research conducted in Denpasar using 110 respondents through purposive sampling method. Questionnaires are used to measure 22 indicators and analyzed by using SEM analysis technique and Sobel test. The study found that by increasing advertising and personal selling will directly increase brand awareness and purchase intention. AJB Bumiputera 1912 should ensure that people have enough brand awareness to increase consumer purchase intention. It can be done by ensuring that advertising or personal selling activities has been run well and in accordance with what is expected by prospective customers.
Keywords: advertising; personal selling; brand awareness; purchase intention